Distance Education: problems of theory and contradiction of practice - V. Shevchenko; A. Gladgov (Ìнформаційні технології в освіті, 2009)
The article covers some issues concerning to methodological problems to provide clear determination of the following terms: education forms and learning forms. Also, it determines some terms like “Education Information Environment” and “Learning Information Environment”. In the frame of the distance learning application, the article provides the integrated didactics method for the learning information environment design, based on algorithmical structure with the logical, cross-curriculum and cause-and-effect relations.